Immersive Virtual Reality and Ocular Tracking for Brain Mapping During Awake Surgery: Prospective Evaluation Study - Casanova, Morgane; Clavreul, Anne; Soulard, Gwénaëlle; Delion, Matthieu; Aubin, Ghislaine; Ter Minassian, Aram; Seguier, Renaud; Menei, Philippe (JMIR Publications, 2021)
BackgroundLanguage mapping during awake brain surgery is currently a standard procedure. However, mapping is rarely performed for other cognitive functions that are important for social interaction, such as visuospatial cognition and nonverbal language, including facial expressions and eye gaze. The main reason for this omission is the lack of tasks that are fully compatible with the restrictive environment of an operating room and awake brain surgery procedures. ObjectiveThis study aims to evaluate the feasibility and safety of a virtual reality headset equipped with an eye-tracking device that is able to promote an immersive visuospatial and social virtual reality (VR) experience for patients undergoing awake craniotomy. MethodsWe recruited 15 patients with brain tumors near language and/or motor areas. Language mapping was performed with a naming task, DO 80, presented on a computer tablet and then in 2D and 3D via the VRH. Patients were also immersed in a visuospatial and social VR experience. ResultsNone of the patients experienced VR sickness, whereas 2 patients had an intraoperative focal seizure without consequence; there was no reason to attribute these seizures to virtual reality headset use. The patients were able to perform the VR tasks. Eye tracking was functional, enabling the medical team to analyze the patients' attention and exploration of the visual field of the virtual reality headset directly. ConclusionsWe found that it is possible and safe to immerse the patient in an interactive virtual environment during awake brain surgery, paving the way for new VR-based brain mapping procedures. Trial RegistrationClinicalTrials.gov NCT03010943; https://clinicaltrials.gov/ct2/show/NCT03010943.